PENGARUH LAMA STRES NUTRISI PENGHENTIAN PUPUK AB MIX TERHADAP MUTU INTERNAL DAN FISIK BUAH MELON (CUCUMIS MELO L.) VARIETAS GOLDEN AROMA - Muhammad Yusuf; Rennanti Lunadiyah Aprilliya (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2026)
Effect of Nutrient Stress Duration by Termination of AB Mix Fertilizer on Internal and Physical Quality of Melon (Cucumis melo L.) Variety Golden Aroma. This study was conducted to evaluate the effect of nutrient stress duration through termination of AB Mix fertilizer application on internal and physical fruit quality of greenhouse-grown melon. The experiment used a Completely Randomized Design (CRD) with one factor consisting of five stress durations (2, 3, 5, 6, and 7 days) with five replications. Observed parameters included fruit weight, fruit diameter, net thickness, flesh thickness, total soluble solids (°Brix), and fruit water content. Data were analyzed using analysis of variance (ANOVA) at a 5% significance level followed by LSD test when significant differences were detected. The results indicated that stress duration significantly affected fruit sweetness and highly significantly affected water content, while no significant effect was observed on physical fruit parameters. A moderate stress duration of 3 days produced the most optimal quality combination by increasing °Brix without significantly reducing physical fruit characteristics.